Postmodern Eschatology? - Webster, Karl (Toronto journal of theology, 1999)
The question mark in my title is very deliberate. It is meant to qualify both terms: "postmodern" and "eschatology." There is a question mark against "postmodern" because, as I shall try to show, I am unconvinced that postmodernity is the determining factor in responsible Christian theology; and, accordingly, there is a question mark against "eschatology" because I am also unconvinced that a postmodern eschatology is either necessary or possible. Christian eschatology, I want to suggest, will only be worthy of the title if it allows itself to be led all along the line by the witness of Holy Scripture and if it modestly and humbly, and yet also with courage and astonishment, tries to indicate what it finds there. Its essential task, whether in postmodernity, modernity or premodernity is one of patient, respectful attentiveness to the biblical testimony allowing itself to be shaped by the hope which is there expressed, and quietly letting that hope disturb, shatter and remake human thought and action.